Right skills for the job? : rethinking training policies for workers - Almeida, Rita [Herausgeber]; Behrman, Jere [Herausgeber]; Robalino, David [Herausgeber] (The World Bank, 2012)
In most of the industrialized countries, the acquisition of knowledge and skills is the entrance card to rewarding jobs and a better payment for the individual, but also crucial to enable economic diversification and productivity growth. In the developing world, things look much more different: the majority of workers have a very low level of education. Common to the work force in developing countries is also a mismatch of skills workers have and those employers demand. A recent empirical study shows that not only technical skills guarantee a sustainable access to the labor market. There is a growing need of cognitive and non-cognitive skills, which are acquired in early childhood and in primary and secondary education. The demand for higher level cognitive skills seems to correlate with the growing development and diversification of a country's labor market. This book discusses how current training policies and programs in developing countries need to change to improve education levels and skills development. For this purpose, the authors discern three types of training programs relevant for school leavers or those who are already in the labor market: pre-employment technical vocational education and training (TVET), on-the-job-training (OJT), and training-related active labor market programs (ALMPs). (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.2 Arbeitsmarkt; S 1.2 Berufsvorbereitung; L 2.1.1 Informelles Lernen; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.3 Außereuropäische Regionen; Bildungspolitik; Aktivierende Arbeitsmarktpolitik; Kompetenzentwicklung; Berufsvorbereitung; On-the-job training; Qualifizierungsmaßnahme; Entwicklungsländer